A theoretical study on country brand and its management - Maria Gabriela Montanari; Janaina de Moura Engracia Giraldi (Internext: Revista Eletrônica de Negócios Internacionais, 2018)
This paper presents a theoretical study in order to clarify the concept of country brand, differentiating it from country image and country of origin effect, and also detail its management, exploring its complexity and differences from the brand management of products and services. Based on the literature, we found that the country brand is derived from a management process, the country branding, which seeks to differentiate between the nation and its offerings in the international market based on their culture. This process involves since the creation of the country brand to its communication to the various target audiences, is more complex than for goods and services, and should consider the elements of country’s identity, positioning and image. The country image is often the focus of branding actions because consists of the associations of the country that international consumers hold in their memory and is considered a tool that can increase the power of the country brand. Thus, it was possible to contribute both to the country brand theory and management, and to governments by providing relevant information to help in defining strategic actions in relation to the country brand and its image.